Transformasi Peran Masjid pada Zaman Modern (Studi kasus di Masjid Nahdlatul Athfal desa Tanjung Kuaw, Seluma) - Norman Ilhami, Olgi; Juki Hardi, Namang; Anggraini, Anisa; Yolanda, Selly; soleha, anisa putri; Gustriani, Anisa; Agustin, Vevi; Hasanah, Ismanur; Oktarina, Wini; Nabila, Maretin; Revola, yashori (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This research aims to know and understand the transformation of the role of mosques in the modern era, the factors that influence it and the impact of this role transformation on the surrounding community. The research locus is Nahdlatul Athfal Mosque located in Tanjung Kuaw, Seluma, Banten Province. This research uses a qualitative approach, which is research that uses a naturalistic approach to find an understanding of phenomena in a special contextualized setting. The conclusion of this study shows that the transformation of the role of mosques in modern times has a significant impact in meeting the spiritual, social and religious needs of the surrounding community. Factors that influence are: social and cultural changes, mosque leadership, congregational participation, relationships with other institutions and communities, and understanding of the needs and aspirations of the surrounding community. The impact of this role transformation is seen in strengthening religious identity, religious education and guidance, social empowerment, character and ethics development, and encouraging solid community life Nahdlatul Athfal Mosque located in Tanjung Kuaw, Seluma have successfully adapted to the changing times and taken on a broader role in improving the quality of life and strengthening social ties within the community.